Satire, Parody and Scatology in Roald Dahl’s Children Literature - Patricia MARTÍN ORTIZ (Aula, 2009)
The purpose of this paper is to analyse the humouristic element in Roald Dahl´s children literature. It is shown how the author writes a satire about society and politics. It is also seen his way of recreating fairy tales, doing a parody of classic characters and endowing them with qualities opposite to those they have in the original work. It is also seen how nonsense is the basis for many stories in his narrative and those jokes which are referred to dirt or body functions that connect so easily with children’s sense of humour. An attempt is made in this article to show the humouristic elements that the author uses to attract the reader’s attention.